1109 Hypoglossal Nerve Stimulation for Treatment of Patient with Severe Obstructive Sleep Apnea (OSA) Complicated by Severe Bruxism. (27th April 2018) - Hamdan, H; Jaumally, B A; Chan, T; Munn, L; Khawaja, I S; Bernardo, E J; Lee, W Y; Carter, G S; Khan, S
Abstract: Introduction: Hypoglossal nerve stimulation (HGNS) has emerged as an effective treatment for obstructive sleep apnea (OSA). Bruxism is a sleep disorder that occurs in 8% of the general population. Safety of HGNS in OSA patients with bruxism has been unclear. Indeed, the relationship between OSA and bruxism remains controversial. We report the first case of severe OSA complicated by bruxism but treated successfully with HGNS. Report of Case: A 56 year old Caucasian male with past medical history of Hodgkin's lymphoma in remission, depression, bruxism managed by a dental guard and OSA presented with the complaints of excessive daytime sleepiness, snoring and witnessed respiratory pauses at night. He had severe facial contact dermatitis upon usage of multiple types of PAP masks. He tried a mandibular advancement device but it was damaged due to bruxism. He received Botox injections at intervals for bruxism and had improvement of bruxism with this treatment. An in-lab sleep study showed severe OSA with an apnea-hypopnea index (AHI) of 57.6 per hour and significant bruxism. A drug induced sleep endoscopy showed him to be a good candidate for HGNS. After placement and activation of the HGNS device he had significant improvement in his snoring, sleep quality, daytime sleepiness and mood. There was no evidence of tongue injuries with HGNS use. One month after activation a HGNS titration sleep study revealed significant improvement in sleep efficiency, oxygenation, AHI and bruxism at target amplitude. A home sleep study with the HGNS device active at target amplitude showed an AHI of 4.9 per hour. Conclusion: HGNS is an effective treatment for patients with OSA complicated by bruxism. Presence of bruxism is not a contraindication for HGNS therapy.